Explanations - Thomas Graeber; Christopher Roth; Constantin Schesch (CESifo GmbH, 2024)
When people exchange ideas, both truths and falsehoods can proliferate. We study the role of explanations for the spread of truths and falsehoods in 15 financial decision tasks. Participants record the reasoning behind each of their answers with incentives for accuracy of their listeners' responses, providing over 6,900 unique verbal explanations in total. A separate group of participants either only observe one orator's choice or additionally listen to the corresponding explanation before making their own choice. Listening to explanations strongly improves aggregate accuracy. This effect is asymmetric: explanations enable the spread of truths, but do not curb the contagion of falsehoods. To study mechanisms, we extract every single argument provided in the explanations alongside a large collection of speech features, revealing the nature of financial reasoning on each topic. Explanations for truths exhibit a significantly richer message space and higher argument quality than explanations for falsehoods. These content differences in the supply of explanations for truths versus falsehoods account for 60% of their asymmetric benefit, whereas orator and receiver characteristics play a minor role.
Keywords: 330; explanations; social learning; speech data; financial knowledge; financial reasoning